The biotechnological importance of the plant-specific NAC transcription factor family in crop improvement - Singh, Sadhana; Koyama, Hiroyuki; Bhati, Kaushal K.; Alok, Anshu (Journal of Plant Research, 2021)
Climate change, malnutrition, and food insecurity are the inevitable challenges being faced by the agriculture sector today. Plants are susceptible to extreme temperatures during the crucial phases of flowering and seed development, and elevated carbon levels also lead to yield losses. Productivity is also affected by floods and droughts. Therefore, increasing plant yield and stress tolerance are the priorities to be met through novel biotechnological interventions. The contributions of NAC genes towards enhancing plant survivability under stress is well known. Here we focus on the potential of NAC genes in the regulation of abiotic stress tolerance, secondary cell wall synthesis, lateral root development, yield potential, seed size and biomass, ROS signaling, leaf senescence, and programmed cell death. Once naturally tolerant candidate NAC genes have been identified, and the nature of their association with growth and fitness against multi-environmental stresses has been determined, they can be exploited for building inherent tolerance in future crops via transgenic technologies. An update on the latest developments is provided in this review, which summarizes the current understanding of the roles of NAC in the establishment of various stress-adaptive mechanisms in model and food crop plants.